Digital Tracking as a Political Program - Jeanette Hofmann (WZB Berlin Social Science Center, 2020)
Even in exceptional times, surveillance remains a political program rather than an imminent force.
Keywords: 300; computer; contagious disease; Coronavirus; COVID-19; epidemic; digital media; monitoring; software